Keefektifan Model Pembelajaran Problem Based Learning terhadap Keaktifan Belajar Siswa Tema 9 Kelas V SDN Sokopuluhan 02 Pati - Utomo, Muhammad Budi (Lembaga Yasin AlSys, 2023)
Students are less active when learning takes place, learning outcomes in theme 9 subjects are still low and teachers are still experiencing problems in using learning methods. The problem in this study is whether the use of the Problem Based Learning Learning Model is Effective for Student Learning Activeness in Theme 9 SDN Sokopuhan 02 Pati? The goal achieved in this study was to find out whether the Problem Based Learning Learning Model Against Student Learning Activeness Theme 9 SDN Sokopuhan 02 Pati. This type of research is quantitative. The research design used a Pre-Experimental Design in the form of a One Group Pretest Posttest Design. The population in this study were students of SDN Sokopuhan 02 Pati. The sample used was the fifth grade students at SDN Sokopuhan 02 pati which consisted of 13 students. The sampling technique in this study is to use saturated sampling. The data in this study were obtained through tests, interviews and documentation. The data analysis technique used in the initial analysis is the normality test. The final analysis uses the normality test, hypothesis test, level of difficulty, reliability test, individual learning completeness test and class learning mastery test. The results of calculating the pretest and posttest data have a sig value. 0.613 and 0.658 or greater than 0.05. So it can be concluded that the pretest and posttest data are normal. So that it can be continued to the next ketahap. It is known that the t-count price is 7.622 greater than the t-table price which is 7.622 (7.622> 2.728), meaning that ha is accepted and Ho is rejected. Ha accepted means that there is a difference in the average score in the multiple choice questions between the post-test and pre-test. A positive t-count value indicates that the average post-test result is higher than the average pre-test result. So the PBL learning method is effective on student activity in Class V Theme 9. For students, students must be active, creative, and critical in learning so that they can improve the quality of learning by having better thinking skills and active learning.